2018
DOI: 10.2478/vzoo-2018-0028
|View full text |Cite
|
Sign up to set email alerts
|

Helminths of the Mallard, Anas Platyrhynchos (Aves, Anatidae), in Ukraine: Analysis of the Diversity in Mixed Forest Zone and the Black Sea Region

Abstract: Thirty-eight Mallards were collected on the territory of Ukrainian Polissia to study the fauna of their gastro-intestinal helminths. Materials were collected in 1998-2000, 2014 and 2016 on the territory of Volyn and Chernihiv Regions. In total, 33 species of helminths were found. Th e prevalence of cestode infection was 78.9 %. We found 18 cestode species: Aploparaksis furcigera, Cloacotaenia megalops, Dicranotaenia coronula, Diorchis acuminatus, D. stefanskii, Fimbriaria fasciolaris, F. teresae, Microsomacant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This stands in contrast to most literature on the nematodes of mallards. Pav & Zajicek (1963), Birova & Macko (1984), Fedynich & Pence (1994), Kavetska et al (2008), Yoshino et al (2009) and Syrota et al (2018) identified between four and nine species. Only De Jong (1976) reported negative results from mallards from the Netherlands.…”
Section: Nematodamentioning
confidence: 97%
See 1 more Smart Citation
“…This stands in contrast to most literature on the nematodes of mallards. Pav & Zajicek (1963), Birova & Macko (1984), Fedynich & Pence (1994), Kavetska et al (2008), Yoshino et al (2009) and Syrota et al (2018) identified between four and nine species. Only De Jong (1976) reported negative results from mallards from the Netherlands.…”
Section: Nematodamentioning
confidence: 97%
“…The acanthocephalan species recovered in this study accord well with other studies from this host. Specimens of the genus Polymorphusnamely, P. minutus and its junior synonym P. magnus (the status of P. magnus is discussed in the introduction) and F. anatis are the two taxa recorded from Europe (Pav & Zajicek, 1963;Macko, 1979;Birova & Macko, 1984;Kavetska et al, 2008;Crompton & Harrison, 2009;Syrota et al, 2018). One other acanthocephalan genus, Corynosoma, was recorded in mallards from North America, the species being Corynosoma constrictum Van Cleave, 1918(Van Cleave & Starrett, 1940Fedynich & Pence, 1994).…”
Section: Acanthocephalamentioning
confidence: 99%